1984
DOI: 10.1056/nejm198407053110102
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Sickle Hemoglobinopathies on Growth and Development

Abstract: To determine the influence of hemoglobinopathy on growth and development, we examined the height, weight, and sexual maturation of 2115 patients 2 to 25 years old who had homozygous sickle-cell disease (SS), SC disease (SC), sickle beta+ thalassemia (S beta+), or sickle beta O thalassemia (S beta O). Using regression analysis of these cross-sectional data to generate growth and maturation curves for each hemoglobinopathy, we found that the curves for all hemoglobinopathy groups were significantly different fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
124
2
10

Year Published

1985
1985
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 198 publications
(145 citation statements)
references
References 27 publications
9
124
2
10
Order By: Relevance
“…All 4 genotypes were below norms for African Americans. 4 Growth differences were evident even in the youngest group of children (2-4 years old). Numerous other studies have confirmed these observations.…”
mentioning
confidence: 95%
“…All 4 genotypes were below norms for African Americans. 4 Growth differences were evident even in the youngest group of children (2-4 years old). Numerous other studies have confirmed these observations.…”
mentioning
confidence: 95%
“…27 Growth defi cit tends to be greater in width than in height or length and is more severe in patients with sickle cell anemia. 28 The higher cranial index recorded in the sickle cell group corresponds to the brachycephalic head shape dominant in this group. Even though, the brachycephalization is more pronounced in the female sickle cell disease children where all the age groups are brachycephalic except for age group 8-11 years as against the sickle cell males where only age group 12-15 years is brachycephalic all the remaining age groups had the mesocephalic head shape as dominant.…”
Section: Discussionmentioning
confidence: 92%
“…8,9 Poor growth has been previously documented in SCA. [10][11][12] However, the causes and clinical significance are not well understood. 13 In Africa, where dietary intakes are sub-optimal for many populations, we hypothesized that nutrition is an important modifiable risk factor for SCA morbidity and that poor nutritional status is associated with increased mortality and morbidity.…”
Section: Introductionmentioning
confidence: 99%